Solusi Numerik Model Matematika SIRI Metode Perturbasi Homotopi dalam Penggunaan E-money Sistem E-parking - Ihsan, Hisyam; Zaki, Ahmad; Syuaiba, Nur (Journal of Mathematics, Computations and Statistics, 2022)
This research is an applied research about application of the Homotopy Perturbation method to solve numeric solution of SIRI model in the use of E-money in E-parking system. The data that used in this research is a data which obtained by share the questionnaires to 236 respondents randomly at the research location at Panakkukang Mall, Nipah Mall and Ratu Indah Mall . This research starts from setermining general solution with Homotopy Perturbation method, parameter decision, simulation and result analyzis. This research gets movement graphic and resukt analyzis from SIRI model by riil data. The conclutions gets that the Homotopy Perturbation method can be used to analyze the preference of using E-money in E-parking system also can be a consideration by various parties to maximize the role of the use of E-money in various aspects in life, especially in E-parking.